Seasonal Variations of Surface Radio Refractive Index in Mongolia - S, Jamiyan; J, Battogtokh; O, Tsendayush; J, Nyamjav (Scientific transaction of the National University of Mongolia. Physics, 2022)
In this paper, the statistical analysis of surface radio refractivity in Mongolia is studied. The method proposed in the recommendation of the International Telecommunication Union ITU has been used. Meteorological data derived from fifty nine weather stations which cover the most populated areas in Mongolia. A total of more than five million refractivity measurements was considered in this analysis. The result showed that the highest average values of the radio refractivity were observed in January while the lowest values were observed in April and May. The annual refractivity values were higher in the northern region and lower in the southern part of the geographical map. The monthly maximum radio refractivity value, 342 N-Units was in Zavkhan aimag in January. The lowest value was 290 N-Units in Umnugovi aimag in May. The result also shows that the seasonal refractivity variation is caused follows the climatic condition and geographical region.